Perlindungan Konsumen Terhadap Praktik Gesek Tunai Pada Layanan Shopee PayLater - asyiah, siti; Sadiani Sadiani; Muhammad Amin (JURNAL USM LAW REVIEW, 2025)
Digital financial innovation has enabled the rapid expansion of PayLater services, yet misuse in the form of cash swipe (Gestun) transactions creates significant legal problems due to fictitious purchases, contractual defects, and weak consumer protection. This study aims to analyze the legal protection afforded to consumers involved in Gestun practices on Shopee PayLater by integrating perspectives from positive law, Islamic law, and empirical findings from affected users. Using a juridical-empirical method supported by statute, conceptual, and doctrinal analysis, this research collects primary data from consumers who suffered financial losses and individuals involved in Gestun mechanisms. The findings indicate that Gestun does not meet the legal requirements of a valid contract, violates consumer protection norms under the Consumer Protection Law and the Electronic Information and Transactions Law, and contradicts Islamic principles due to elements of gharar, tadlis, and invalid akad. The study further reveals substantial gaps between normative regulation and actual consumer experiences, exacerbated by limited supervision of digital financing services. This research proposes regulatory reform, stronger enforcement, and enhanced digital legal literacy as essential measures to prevent Gestun practices and strengthen consumer protection within Indonesia’s digital financing ecosystem.   Inovasi keuangan digital telah mendorong perluasan layanan PayLater, namun penyalahgunaan dalam bentuk jasa gesek tunai (Gestun) menimbulkan persoalan hukum karena melibatkan transaksi fiktif, cacat perjanjian, dan lemahnya perlindungan konsumen. Penelitian ini bertujuan menganalisis bentuk perlindungan hukum terhadap konsumen dalam praktik Gestun pada Shopee PayLater melalui pendekatan hukum positif, hukum Islam, dan temuan empiris dari pengguna yang mengalami kerugian. Metode yang digunakan adalah yuridis-empiris dengan analisis peraturan perundang-undangan, konsep hukum, doktrin, serta data primer dari konsumen dan pihak terkait dalam mekanisme Gestun. Hasil penelitian menunjukkan bahwa Gestun tidak memenuhi syarat sah perjanjian, melanggar ketentuan UU Perlindungan Konsumen dan UU ITE, serta bertentangan dengan prinsip muamalah karena mengandung unsur gharar, tadlis, dan akad yang tidak sah. Temuan empiris juga mengungkap adanya kesenjangan antara norma hukum dan praktik faktual serta minimnya pengawasan terhadap layanan pembiayaan digital. Penelitian ini merekomendasikan penguatan regulasi, peningkatan penegakan hukum, dan literasi hukum digital untuk mencegah praktik Gestun dan memperkuat perlindungan konsumen dalam ekosistem pembiayaan digital di Indonesia.